2020
DOI: 10.21608/jppp.2020.96009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Insecticidal Activity of Three Forms of Silica Nanoparticles on some Main Stored Product Insects

Abstract: The control of stored grain pests requires effective materials that are save for humans and environment, low cost, available and easy to obtain and do not need trained labor. Therefore, the current study suggested testing three silica forms in the form of nanoparticles, these were Aerosil 200, chemical and bio-silica for controlling Callosobrochus maculatus F. (Col., Bruchidae), Rhythopertha dominica fab, and Tribolium confusum (Jacquelin du Val). The obtained results showed that the percent mortality increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…A significant increase in mortality was observed at high concentrations, and even at lower concentrations, mortality percentages remained high to some extent. The results showed that the increasing SNPs concentration had increased the mortality of treated C. maculatus after 48 h. This was in line with data published by Salem 23 and El-Bendary and El-Helaly 24 , who observed that mortality rate of insects increased by increasing concentrations and exposure times. The tested formulations of silica nanoparticles achieved significant effect against Tribolium confusum, Rhythopertha dominica , and C .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A significant increase in mortality was observed at high concentrations, and even at lower concentrations, mortality percentages remained high to some extent. The results showed that the increasing SNPs concentration had increased the mortality of treated C. maculatus after 48 h. This was in line with data published by Salem 23 and El-Bendary and El-Helaly 24 , who observed that mortality rate of insects increased by increasing concentrations and exposure times. The tested formulations of silica nanoparticles achieved significant effect against Tribolium confusum, Rhythopertha dominica , and C .…”
Section: Discussionsupporting
confidence: 90%
“…The tested formulations of silica nanoparticles achieved significant effect against Tribolium confusum, Rhythopertha dominica , and C . maculatus 23 . In the same context, amorphous SNPs were highly efficient against Sitophilus oryzae and Corcyra cephalonica resulting in over 90% and 100% mortality, respectively, and an increase in exposure time and SNP concentration increased the mortality rate 18 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles toxicity has been demonstrated against many insects such as Sitophilus oryzae (Debnath et al, 2011), mosquitoes, including Anopheles stephensi Liston, Aedes aegypti Linnaeus and Culex quinquefasciatus Say (Barik et al, 2012), cotton leafworm, Spodoptera littoralis (El-bendary and El-Helaly, 2013) and the cowpea seed beetle, Callosobruchus maculatus (F.) (Rouhani et al, 2013 andArumugam et al, 2016). The insecticidal activity of nanosilica was also confirmed by Ziaee and Ganji (2016); Diagne et al (2019);Rouhani et al (2019); Haroun et al (2020) and Salem (2020) against Rhythopertha dominica F., Tribolium confusum Jacquelin du Val., Caryedon serratus (Olivier), Tribolium castaneum Herbst., C. maculatus F., and Sitophilus granarius (L.).…”
Section: Discussionmentioning
confidence: 93%
“…All the tested materials caused mortality of adult and offspring of the three tested insects, and mortality increased with the increase of concentration and exposure period. The adults C. maculatus were more susceptible followed by R. dominica and T. confusum with the three tested materials at all concentrations used (Salem, 2020).…”
Section: Silicon Dioxide Nanoparticles (Sio 2 Nps)mentioning
confidence: 87%